Conformation of poly(dG-dC) . poly(dG-dC) modified by the carcinogens N-acetoxy-N-acetyl-2-aminofluorene and N-hydroxy-N-2-aminofluorene. - Sage, E (1980)
Poly(dG-dC) . poly(dG-dC) was modified by reaction with N-acetoxy-N-acetyl-2-aminofluorene (N-AcO-AAF). Two samples with 6.6% and 8.5% modified bases were prepared. The modified bases are randomly distributed along the polymer chain, as deduced from competition experiments between antibodies against N-2-(guanosin-8-yl)-acetylaminofluorene, modified poly(dG-dC) . poly(dG-dC), and modified DNAs. Circular dichroism studies show that poly(dG-dC) . poly(dG-dC) modified by N-AcO-AAF is much more sensitive to the addition of alcohol than poly(dG-dC) . poly(dG-dC). In about 50% (vol/vol) alcohol, both polynucleotides have the same conformation, which is the Z form or a Z-like form. Moreover, in low salt and in the absence of alcohol, poly(dG-dC) . poly(dG-dC) modified by N-AcO-AAF is partially in the Z form. Poly(dG-dC) . poly(dG-dC) modified by N-hydroxy-N-2-aminofluorene can also adopt the Z form, but the transition is induced at a higher percentage than that of poly(dG-dC) . poly(dG-dC) modified by N-AcO-AAF. In low salt and in the absence of alcohol, no Z form was detected in poly(dG-dC) . poly(dG-dC) modified by N-hydroxy-N-2-aminofluorene.